Strengthening Knowledge of AI-based applications to facilitate the preparation of learning media for teachers at TKIT Mekar Insani Minggiran Yogyakarta - Witanti, Arita; Soeharto, Triana Noor Edwina Dewayani; Apriani, Nana (Edumedia Solution, 2025)
Artificial intelligence (AI) technologies offer transformative opportunities in educational settings, particularly for teachers who are preparing interactive learning materials for early childhood education (ECE). However, challenges persist in their implementation, such as limited teacher knowledge, infrastructure barriers, and ethical concerns. This study aims to enhance teachers' knowledge at TKIT Mekar Insani, Yogyakarta, by providing training through mini workshops and supporting resources, such as refurbished computers. The program involved 25 teachers and included pre- and post-training evaluations. Results indicate a significant increase in teachers' ability to use AI-based tools, demonstrated by the production of engaging learning materials and improved confidence in integrating technology into their pedagogy. This initiative highlights the importance of bridging technology gaps in educational institutions and fostering continuous professional development.